Effects of Crop Geometry and Nutrient Management On Nutrient Uptake and Quality Parameters of Potato Under Winter Maize + Potato Intercropping System (Bangladesh Journal of Botany, 2021)
Effects of crop geometry and nutrient management on nutrient uptake and quality parameters of potato under winter maize + potato intercropping system were studied during two consecutive years (2015-2016 and 2016-17) at BHU, Varanasi, India. Results revealed that under different crop geometry the nutrient uptake (NPK kg/ha) were obtained significantly higher with 1 : 2 row ratio in additive series as compared to other row ratio due to maximum plant population. The minimum nutrient uptake (NPK kg/ha) were obtained with 1:1 row ratio in replacement series. However, quality parameters (protein and starch) did not vary significantly by different crop geometry during both the years of investigation. Amongst nutrient management, the highest nutrient uptake (NPK kg/ha) and quality parameters (protein and starch) were obtained significantly with the application of 100% RDF + 25% N through poultry manure followed by the application of 100% RDF + 25% N through vermicompost. Thus, the results suggest that 1:2 row ratio (crop geometry) in additive series with 100% RDF + 25% N through poultry manure (nutrient management) followed by 100% RDF + 25 % N through vermicompost were feasible and practicable during both the years of investigations.Bangladesh J. Bot. 50(4): 1011-1019, 2021 (December)